Enhanced Nagios core implementation in network monitoring / Hasrul Azwar Ismail @ Ishak - Ismail @ Ishak, Hasrul Azwar (2014)
The rapid growth of network technology currently allows the diversity and integrated of network equipment with each other. With these increases, manage network equipment’s heterogeneity is a big challenge to network administrators. The network monitoring system is essential for straightforwardly and quickly managing the network equipment’s. Through this research, an open source application was used to monitor and analyze network equipment and data centers. An open source tool is used because it can manage simply and efficiently. Other than that, an open source application is preferred because it is free and all the codes are open. The network monitoring tools also can be modified to suit with the existing network environment. Nagios Core was chosen to be used in this research. The main objective of this research is to enhance Nagios Core implementation in configuration management, visualization, graphing system and notification alert. The next objective is to test the effectiveness of enhancing Nagios Core implementation in monitoring and analyzing UNISEL network and data center. Default version of Nagios Core is not user friendly. The notification alert process also matters to be considered in this research. This is important because the network monitoring system and data centers need to be equipped with the ability to provide instant notification. This is essential to allow for immediate action by the network administrator.